Weatherability of conventional and nanocomposites of LDPE and Zinc Oxide. Issue 2 (22nd June 2015) - Redhwi, Halim Hamid; Siddiqui, Mohammad Nahid; Andrady, Anthony L.; Muhammad, Younas; Syed, Hussain
Abstract : LDPE thermoplastic composites prepared using 1–4 wt% of conventional filler‐grade ZnO and nanoscale ZnO were investigated to determine whether the presence of either grade of filler affected the weatherability of the composite material. Outdoor exposure (natural weathering) studies and accelerated weathering was performed and tensile properties were used to assess the weather‐induced damage. Weatherability under outdoor exposure and under laboratory‐ accelerated conditions, primarily quantified using tensile properties, were found to be the same for composites with conventional and nanoscale ZnO filler. POLYM. COMPOS., 38:341–348, 2017. © 2015 Society of Plastics Engineers